Adventures in babysitting [videorecording (DVD)] - Columbus, Chris; Shue, Elisabeth; Coogan, Keith, 1970-; Rapp, Anthony (Touchstone Home Video, 1999)
A babysitter and three kids leave the safe suburbs and head for the heart of the big city to rescue a frantic friend.